Formation of climate coalitions and preferential free trade: the case for participation linkage - Thomas Kuhn; Radomir Pestow; Anja Zenker (Environmental Economics and Policy Studies, 2023)
We study the endogenous formation of climate coalitions linked to a preferential free trade arrangement. In a multi-stage, micro founded strategic trade and participation game, coalition and fringe countries dispose of a discriminatory tariff on dirty imports as well as emission permits imposed on domestic producers. Permits are traded on a common permit market inside the coalition and on local markets outside, respectively. We provide an analytical solution for the general equilibrium and the policy game, in the three country case, while the participation game is solved by Monte Carlo simulation. Moreover, conditional probabilities are computed for the transition to coalitions of various sizes induced by free trade. Under various regimes analyzed, we find that preferential free trade can create strong incentives for building effective climate coalitions in terms of depth and breadth. This result even holds if fringe countries are given the option of trade cooperation as a retaliation devise and is driven by a favorable shift in the coalition's terms of trade. As a policy implication, negotiations on international climate treaties and free trade arrangements should be interlinked.
Keywords: Q54; Q56; F18; F15; Q58; 330; Climate change; International environmental agreements; Preferential free trade; Issue linkage; Emission permits